Bioethanol Production from Tea Waste as a Basic Ingredient in Renewable Energy Sources - Muhammad Khairul Afdhol; Hafni Zulaika Lubis; Chalidah Pratiwi Siregar (Universitas Islam Riau (UIR) Press, 2019)
Global demand for energy needs has increased due to the rapid development of the human population, raising the industrial prosperity in developing countries. Primary energy demand is still supplied from fossil fuels, such as oil, coal and natural gas. The utilization of fossil fuels will continuously enhance the effect of greenhouse gases in the atmosphere. On the other hand, the extent of the tea plantation area in Indonesia reached 53,009 Ha, so that it will reproduce a waste too. Thus, spent tea as bioetanol. In addition it contains cellulose fibres are quite high, environmentally friendly and economical. Bioethanol as motor vehicle fuels can reduce the addition of CO2 at atmosphere because the use of biomass for the production and usage of bioethanol can be considered as a closed cycle. According to this principle the buyer of CO2 from fuel combustion bioethanol originating from the CO2-based biomass will be reabsorbed by plants through photosynthesis reactions. As a result of this whole process is not accounted for emissions of CO2 liquid gas a greenhouse gas into the atmosphere. Bioethanol-cellulosa can reduce greenhouse gas emissions amounted to 80%. The process into products bioethanol via hydrolysis, fermentation, distillation and characterization using Gas Chromatography-Mass Spectrometry (GC-MS). Them is the optimal bioethanol levels produced from fermented inoculant 1% amounting to 8.2% and optimal levels of bioethanol produced from hydrolysis of 8% H2SO4 results amounted to 8.2%, thus optimumsitas the ethanol produced from 8% acid and 1% inoculant apply to have levels of ethanol amounted to 8.2%. The product program could be developed into bioethanol solvent to dissolve the oil that is waxy crude oil.